The red flashes of Folkmarketing Coca Cola's strategy with the Bolivian salteña - Calvimontes Diaz, Vanessa (2022)
This article analyzes a case study that is part of the current of Folkcommunication and marketing. The romantic story created between a typical Bolivian food, the salteña, and the American drink, Coca Cola. This relationship arises from a communication strategy of the transnational, which responds to an appropriation of cultural aspects, which is not only developed in Bolivia, but also in other countries of the world. The article initially details some aspects related to the two main actors in this story, then describes the case, emphasizing the most outstanding communication aspects, to finally analyze all the elements in light of the concepts of folk communication and marketing.